KEABSAHAN RUISLAG BARANG MILIK DAERAH DENGAN TANAH MILIK YAYASAN - Dyah Hapsari Prananingrum; Ninon Melatyugra (Refleksi Hukum: Jurnal Ilmu Hukum, 2020)
Ruislag is a legal act conducted by the Local Government to optimize its assets, in which one of its forms is exchanging its assets with private assets. In practice, ruislag involves a foundation that owns assets, for instance, land ownership, as a party in ruislag. This article prescribes two main points that shall be noticed by the Local Government and the Foundation regarding the legitimate ruislag conduct. Those two main points highlight the organization of the foundation issue and the administrative aspects of legal documents of the land owned by the foundation, particularly the land that was obtained by a grant. This article uses a conceptual approach and a statutes approach in its analysis.